2016
DOI: 10.1002/wrna.1369
|View full text |Cite
|
Sign up to set email alerts
|

The organization and regulation of mRNA–protein complexes

Abstract: In a eukaryotic cell, each messenger RNA (mRNA) is bound to a variety of proteins to form an mRNA–protein complex (mRNP). Together, these proteins impact nearly every step in the life cycle of an mRNA and are critical for the proper control of gene expression. In the cytoplasm, for instance, mRNPs affect mRNA translatability and stability and provide regulation of specific transcripts as well as global, transcriptome‐wide control. mRNPs are complex, diverse, and dynamic, and so they have been a challenge to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 164 publications
(382 reference statements)
1
39
0
Order By: Relevance
“…Mammalian mRNA half-lives vary extensively in vivo (Lugowski et al, 2018;Schwanhäusser et al, 2011), and a major question has been which processes and regulatory elements underlie this variation. In mammals, the 3' untranslated region (UTR) is a hotspot for regulation, containing the majority of instability-promoting sites, such as AU-rich elements or microRNA-binding sites (Bartel, 2009;Rissland, 2016;Shyu et al, 1989;Xu et al, 1998). Typically, instability-promoting motifs accelerate decay by eventually recruiting deadenylation-dependent decay machinery and stripping stabilizing mRNP components (Eulalio et al, 2009;Fabian et al, 2011;2009;Kuzuoğlu-Öztürk et al, 2016;Rissland et al, 2017;Zekri et al, 2013) We have previously demonstrated that codon usage is a key mechanism underlying mRNA half-life variability in S. cerevisiae such that changes in overall "optimal" and "non-optimal" synonymous codon composition manifest as dramatic changes in mRNA stability (Presnyak et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian mRNA half-lives vary extensively in vivo (Lugowski et al, 2018;Schwanhäusser et al, 2011), and a major question has been which processes and regulatory elements underlie this variation. In mammals, the 3' untranslated region (UTR) is a hotspot for regulation, containing the majority of instability-promoting sites, such as AU-rich elements or microRNA-binding sites (Bartel, 2009;Rissland, 2016;Shyu et al, 1989;Xu et al, 1998). Typically, instability-promoting motifs accelerate decay by eventually recruiting deadenylation-dependent decay machinery and stripping stabilizing mRNP components (Eulalio et al, 2009;Fabian et al, 2011;2009;Kuzuoğlu-Öztürk et al, 2016;Rissland et al, 2017;Zekri et al, 2013) We have previously demonstrated that codon usage is a key mechanism underlying mRNA half-life variability in S. cerevisiae such that changes in overall "optimal" and "non-optimal" synonymous codon composition manifest as dramatic changes in mRNA stability (Presnyak et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…hnRNP A1 | protein-RNA specificity | RNA structure | thermodynamics | binding kinetics G ene expression is regulated by an ensemble of protein-RNA complexes that assemble and disassemble throughout the lifetime of a transcript (1)(2)(3)(4)(5). Knowledge of the determinants of RNA-binding protein (RBP) specificity is therefore essential to understanding the relative affinity for sites of association within the transcriptome.…”
mentioning
confidence: 99%
“…It has recently been demonstrated that a class of small, endogenous and non-coding nucleic acid miRNAs are able to prevent transcription of PTEN mRNA (45). According to the current literature, miRNAs have a high level of stability in conventional, formalin-fixed, paraffin-embedded clinical tissue specimens, which suggests that they may have potential as diagnostic molecular markers; however, mRNAs tend to be more susceptible to environmental impact and are more unstable than miRNAs (46)(47)(48). Furthermore, it has previously been suggested that miRNAs serve important roles in tumorigenesis via their regulation of protein coding genes (49,50).…”
Section: Discussionmentioning
confidence: 99%